Inclusive teaching strategies and their impact on the academic performance of students with special needs - Vallejo Lucero, Gabriela Alexandra (2025)
The aim of this study was to analyze the relationship between inclusive teaching strategies and the academic performance of students with special educational needs in basic education, identifying the pedagogical and contextual factors that influenced their effectiveness. The research followed a quantitative approach, with a non-experimental, correlational, and cross-sectional design. The population consisted of teachers and students from the Edukat Psychopedagogical Center, working with a census sample. Data were collected through a structured questionnaire and academic record sheets and analyzed using the SPSS statistical software, applying Spearman’s correlation test. The results showed a positive and statistically significant relationship between inclusive teaching practices and academic performance, confirming that differentiated planning, collaborative work, and adaptive assessment contributed to improved learning outcomes. It was concluded that the effectiveness of inclusive education depended on the interaction among pedagogical, institutional, and emotional factors, highlighting the need to strengthen teacher training and inclusive institutional culture. These findings provided empirical evidence of the contribution of inclusive teaching to educational equity and students’ integral development.